The Effect of Reward, Punishment and Workload on Employee Performance at The People's Credit Bank in Palembang City - Pradhana, Nugraha Adhi; Widiyanti, Marlina; Yusuf, Muhammad; WK, Wita Farla (International Journal Labs, 2024)
This study was conducted with the aim of determining the influence of rewards, punishments, and workload on employee performance at the People's Credit Bank in the city of Palembang. The population in this study is all active employees in the marketing department of the People's Credit Bank in the city of Palembang who are still actively operating in 2024 as many as 14 companies. The sample was taken from a minimal number because the number of the population is not known for sure, so the number of samples in this study is 136 people. The results of multiple linear regression analysis show that rewards, punishments and workload have a positive and significant effect on employee performance. Rewards, gifts and bonus payments to employees who can meet the target or even exceed the set target must be appropriate, fair and transparent and also paid on time. Punishment, it is hoped that this punishment will be given fairly to all employees. Workload, it is hoped that companies can also evaluate the provision of work achievement targets that must be met by employees, especially in the marketing department.